Innovative modification strategies and emerging applications of natural hydrogel scaffolds for osteoporotic bone defect regeneration - Chen, Yanan; Zhao, Qinghua (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoporosis, a prevalent systemic metabolic bone disease, is characterized by diminished bone mass, microarchitectural deterioration of bone tissue, and heightened bone fragility. In osteoporotic patients, chronic and progressive bone loss often leads to fractures and, in advanced cases, critical-sized bone defects. While traditional bone repair approaches are constrained by significant limitations, the advent of bioactive scaffolds has transformed the therapeutic paradigm for osteoporotic bone regeneration. Among these innovations, natural polymer-based hydrogel scaffolds have emerged as a particularly promising solution in bone tissue engineering, owing to their superior biocompatibility, tunable biodegradation properties, and exceptional ability to replicate the native extracellular matrix environment. This review systematically explores recent breakthroughs in modification techniques and therapeutic applications of natural hydrogel scaffolds for osteoporotic bone defect repair, while critically analyzing existing clinical challenges and proposing future research trajectories in this rapidly evolving field.